2008
DOI: 10.1002/ijc.23835
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid synthase inhibition with Orlistat promotes apoptosis and reduces cell growth and lymph node metastasis in a mouse melanoma model

Abstract: Fatty acid synthase (FASN) is the enzyme responsible for the endogenous synthesis of the saturated fatty acid palmitate. In contrast to most normal cells, malignant cells depend on FASN activity for growth and survival. In fact, FASN is overexpressed in a variety of human cancers including cutaneous melanoma, in which its levels of expression are associated with a poor prognosis and depth of invasion. Here, we show that the specific inhibition of FASN activity by the antiobesity drug Orlistat or siRNA is able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
129
0
30

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 155 publications
(202 citation statements)
references
References 47 publications
(60 reference statements)
7
129
0
30
Order By: Relevance
“…4,29,41 In the present study, we demonstrated that FASN inhibition induced the intrinsic pathway of apoptosis in B16-F10 mouse melanoma cells, which was preceded by an increase in both ROS production and cytosolic calcium concentration. In addition, this apoptotic cell death was not dependent on p53 activation or MPT.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…4,29,41 In the present study, we demonstrated that FASN inhibition induced the intrinsic pathway of apoptosis in B16-F10 mouse melanoma cells, which was preceded by an increase in both ROS production and cytosolic calcium concentration. In addition, this apoptotic cell death was not dependent on p53 activation or MPT.…”
Section: Discussionsupporting
confidence: 56%
“…12,16 We have recently shown that the inhibition of FASN activity with the anti-obesity drug orlistat significantly reduced proliferation and promoted apoptosis in the mouse metastatic melanoma cell line B16-F10. 29 In this study, we show that FASN inhibition activates the intrinsic pathway of apoptosis in B16-F10 cells by cytochrome c release and caspase-9 and -3 activation, which were preceded by increased reactive oxygen species (ROS) production and cytosolic calcium concentration. p53 activation and the mitochondrial permeability transition (MPT) were not involved in the orlistat-or cerulenin-induced apoptotic cell death.…”
mentioning
confidence: 82%
See 3 more Smart Citations